Fatores associados ao risco de adoecer por malária na região Sudoeste da Amazônia brasileira : estudo de coorte aberta de base populacional - Oliveira, Elaine Cristina de (2017)
Despite the possibility of prevention and treatment, malaria continues to have a devastating impact on the health of people around the world. Objective: To analyze the factors associated with the risk of falling ill with malaria in the District of Três Fronteiras, Colniza, Mato Grosso. Method: This is an open cohort study carried out in a small town in the south-western region of the Brazilian Amazon, with data collected during cross-sectional evaluation visits carried out in 2011, 2012 and 2013 and monitoring by the national epidemiological surveillance system from 2011 to 2014. The risk of falling ill with malaria was determined by the incidence density of a first recurrent episode of the disease after inclusion in the cohort. The factors associated with this risk were assessed by survival analysis and Cox regression. Results: The incidence of the first recurrent episode of malaria was higher among patients who were infected at the time of their inclusion in the study (HR=5.58; 95%CI: 4.31; 7.22; p<0.001), who reported symptoms at the beginning of their follow-up (HR=1.30; 95%CI: 1.0; 1.69; p=0.049), who worked in logging (HR=1.93; 95%CI: 1.51; 2.48; p<0.001) and who reported 3 to 10 previous episodes of malaria in their lifetime (HR=1.50; 95%CI: 1.09; 2.05; p=0.012). A negative association was found between working in a mining area (HR=0.56; 95%CI: 0.40; 0.77; p<0.001) and having lived between 25% and 50% of their life in a malaria-endemic area (HR=0.54; 95%CI: 0.34; 0.85; p=0.009). The habit of using a mosquito net was not associated (HR=1.27; 95%CI: 0.98; 1.64; p=0.069) with the first recurrent episode of malaria in this cohort. After analysis adjusted for possible confounding effects, only the infection prevalent at study inclusion (HR=4.10; 95%CI: 3.05; 5.51; p<0.001) and working in the logging area (HR=2.16; 95%CI: 1.66; 2.79; p<0.001) remained significantly associated with the occurrence of a first recurrent episode of malaria in the cohort (Table 3). Conclusion: The risk of an individual having a recurrent episode of malaria is 9.1/100 person-years. Considering that P. vivax was the predominant species in the area, this finding is relevant, given the possibility of recurrences and, therefore, a greater chance of circulation of the parasites and transmission of the disease. Working in a logging area or being infected with Plasmodium at the inclusion visit were the only factors associated with the risk of presenting a recurrent episode of the disease during the study period.